Meningkatkan Kreativitas Belajar Siswa melalui Pemanfaatan Media Plastisin Mata Pelajaran Seni Budaya di Kelas VIII.G SMP Negeri 12 Mataram - Ariani, Komang (YASIN, 2023)
This study aims to measure the development of student creativity through the activity of making sculptures using plasticine at SMP Negeri 12 Mataram. The results of research on fostering student creativity through plasticine sculpture at SMP Negeri 12 Mataram can be concluded that: The use of plasticine media can increase creativity in learning Cultural Arts Subjects for class VIII.G students at SMP Negeri 12 Mataram. This can be seen from observing teacher activities and observing student activities in cycle I and cycle II. Thus the increase in teacher activity in learning has increased from 71.88% in cycle I to 90.63% in cycle II. Student activity also increased, namely 72.50% in cycle I, rising to 87.50% in cycle II. Mastery of students towards learning materials showed improvement. This is evidenced by the average value of the daily test results (the average daily test without the use of Plasticine Media 73.69 becomes 77.34 and becomes 80.99 after the use of Plasticine media. The descriptive results of the percentage of learning completeness are, starting from pre- action, cycle I and cycle II have increased significantly from 56.25% to 93.55% and have exceeded the 85% requirement for children who are in the very good category.This shows that plasticine media can improve student creativity very well, which can be seen the range of increased creativity from pre-action to the second cycle of 37.30%.